A Review: Saccharin Discovery, Synthesis, and Applications - Mahmood, Ammar A. Razzak; Al-Juboori, Sahar B. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2020)
Saccharin is firstly synthesized in 1879. It is a very well-known as an inexpensive substitute for sugar as it is a non-caloric sweetener. The article shows the properties, use, metabolism and various synthesis and reactions of saccharine. Moreover, the toxicological reports explain that saccharin is mostly responsible for the bladder tumors observed in the male rats, the relationship between the consumption of saccharin and bladder cancer is afforded by epidemiological studies.  The benefit-risk evaluation for saccharin is hardly to indicate. Saccharin is a sugar substitute, frequently used either in food industry, or in pharmaceutical formulations and even in tobacco products. The chemistry of saccharin is interesting because of it suspected carcinogenous character and the possible use as an antidote for metal poisoning. It appears prudent to evaluate their main properties and applications further.